Development in the area of removable and repositionable polyacrylic pressure-sensitive adhesives - Czech, Z. (Polimery, 2022)
The effects of the type and concentration of three multifunctional isocyanate crosslinking agents on the adhesion of titled pressure-sensitive adhesives (PSA) have been determined. Also the effects of the type and concentration of two groups of modifiers - ethoxylated amines [Formula (1)] and n-octylphenoxy derivatives of polyethylene oxide [Formula (II)] on PSA adhesion have been investigated. Both groups of modifiers decrease peel adhesion and cause PSA moving to the removable and repositionable area. The influence of ageing on the adhesion of PSA, modified with mentioned polyethylene oxide derivative, to various surfaces has been estimated.